Efforts to Prevent the Crime of Money Laundering in the Field of Taxation in Indonesia - Ali Kusumo, Bambang; Ash-shidiqqi, Ellectrananda Anugerah (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
Taxes are the most dominant source of funds from the state in the form of the APBN at present. Because it is the most dominant, it needsto be saved. Many acts of tax violations such as income concealment, tax evasion, tax evasion, falsification of tax documents are often asource of illegal funds which are then laundered through a series of transactions to make them look legitimate and not suspicious. Throughnormative juridical research relying on secondary data, both primary legal materials, secondary legal materials and tertiary legal materials,it was revealed that the factors causing the emergence of money laundering in the field of taxation are: complex tax system, lack of supervisionand law enforcement, cross-border activities, corruption and use of technology. Furthermore, efforts to prevent money laundering in the fieldof taxation are carried out through: Increasing legal awareness, cooperation between institutions, supervision and regulation, training andcounseling, international collaboration, use of technology and strict punishment must be carried out.Keywords: Money laundering crime, Tax, Prevention